Gestation: Preparation process of a woman for her baby's birth La gestación: proceso de preparación de la mujer para el nacimiento de su hijo(a) - HERNÁNDEZ LUZ MERY (Universidad Nacional de Colombia, 2008)
The objective of this research is to describe the meaning of self care of one self as well as of the unborn child based on values, beliefs and practices, for a group of gestating women from the district of Engativá. This is a qualitative ethnographic study using the ethnonursing method developed by Madeleine Leininger. This research was carried out with the participation of 8 gestating women, aged between 18 and 30 years of age, with low risk gestation, who attended prenatal control at the UPA La Española from "localidad 10" in Bogotá, during the period between January and August 2005, who shared on an everyday basis their knowledge and experiences in a natural and spontaneous way with the researcher, who, to achieve this, behaved as a apprentice. Based on this dynamics, the transmission of cultural knowledge by the gestating women was encouraged, and the subject "Gestation: process of preparation of women's cultural knowledge for her child's birth", from which two different cultural domains arise: readiness for their child's birth and appropriate feeding practices. El objetivo de la presente investigación es describir el significado de cuidado de sí y de su hijo(a) por nacer, a partir de sus valores, creencias y prácticas, para un grupo de gestantes de la localidad de Engativá. Es un estudio cualitativo etnográfico con la metodología de etnoenfermería propuesta por Madeleine Leininger. La investigación se desarrolló con la participación de 8 gestantes, entre 18 y 30 años de edad, con gestación de bajo riesgo, que asistían al control prenatal a la Unidad Primaria de Atención La Española de la localidad 10 de Bogotá, durante el periodo comprendido entre enero y agosto de 2005, quienes en su cotidianidad (hogar) compartieron sus conocimientos y experiencias de manera natural y espontánea con la investigadora, quien se comportó como aprendiz. Desde esta dinámica se propició la transmisión del conocimiento cultural por las gestantes y se plantea el tema "La gestación: proceso de preparación de la mujer para el nacimiento de su hijo(a)", del que surgen dos dominios culturales: alistarse para el nacimiento de su hijo(a) y realizar prácticas alimentarias apropiadas.